POLA ASUH ORANGTUA DALAM MEMOTIVASI BELAJAR SISWA SEKOLAH DASAR - Ali Idrus (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstract: Parent's child rearing in motivating elementary school students’ learning.Purpose of this research was to describe forms of parents’ child rearing’ parent in motivating elementary school students’ learning and dominant child rearing conducted by parent in improving elementary school students’ learning motivation of  class IV, V, dan VI at Sekolah Dasar Negeri Kabupaten Muaro Jambi. Research method; survey  with questionnaire instrument to  460 students  respondent.  Research results; quality of   parents’ child rearing with democratic form classified very good, i.e. higher than  means, quality of   parents’ child rearing with authoritarian form can be classified as low in motivating students in learning.  Quality of  students’ learning motivation at Muaro Jambi Region can be classified very good and they had maximum hope and mission toward  learning motivation.Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui bentuk  pola asuh orang tua dalam memotivasi siswa dan pola asuh dominan yang dilakukan oleh orang tua untuk meningkatkan kualitas motivasi belajar siswa kelas IV, V, dan VI pada Sekolah Dasar Negeri Kabupaten Muaro Jambi. Metode penelitian; survay dengan instrumen angket terhadap 460 siswa responden. Hasil penelitian; kualitas pola asuh orang tua berbentuk demokratis tergolong sangat baik yaitu di atas rata-rata, pola asuh orang tua berbentuk otoriter kurang baik untuk memotivasi siswa dalam belajar. Kualitas motivasi belajar siswa di kabupaten Muaro Jambi tergolong sangat baik dan  memiliki harapan dan cita-cita untuk mencapai hasil belajar secara maksimal.